Functional Hallmarks of GABAergic Synapse Maturation and the Diverse Roles of Neurotrophins - Grantyn, Rosemarie; Henneberger, Christian; Jüttner, Rene; Meier, Jochen C.; Kirischuk, Sergei (Frontiers in Cellular Neuroscience, 2011)
Functional impairment of the adult brain can result from deficits in the ontogeny of GABAergic synaptic transmission. Gene defects underlying autism spectrum disorders, Rett’s syndrome or some forms of epilepsy, but also a diverse set of syndromes accompanying perinatal trauma, hormonal imbalances, intake of sleep-inducing or mood-improving drugs or, quite common, alcohol intake during pregnancy can alter GABA signaling early in life. The search for therapeutically relevant endogenous molecules or exogenous compounds able to alleviate the consequences of dysfunction of GABAergic transmission in the embryonic or postnatal brain requires a clear understanding of its site- and state-dependent development. At the level of single synapses, it is necessary to discriminate between presynaptic and postsynaptic alterations, and to define parameters that can be regarded as both suitable and accessible for the quantification of developmental changes. Here we focus on the performance of GABAergic synapses in two brain structures, the hippocampus and the superior colliculus, describe some novel aspects of neurotrophin effects during the development of GABAergic synaptic transmission and examine the applicability of the following rules: 1) Synaptic transmission starts with GABA, 2) Nascent/immature GABAergic synapses operate in a ballistic mode (multivesicular release), 3) Immature synaptic terminals release vesicles with higher probability than mature synapses, 4) Immature GABAergic synapses are prone to paired pulse and tetanic depression, 5) Synapse maturation is characterized by an increasing dominance of synchronous over asynchronous release, 6) In immature neurons GABA acts as a depolarizing transmitter, 7) Synapse maturation implies IPSC shortening due to an increase in alpha1 subunit expression, 8) Extrasynaptic (tonic) conductances can inhibit the development of synaptic (phasic) GABA actions.